A chaotic video steganography technique for carrying different types of secret messages. (May 2022) - Yousefi Valandar, Milad; Ayubi, Peyman; Jafari Barani, Milad; Yosefnezhad Irani, Behzad
Abstract: Increasing the security of data in insecure communication networks is the motivation of researchers to propose different types of methods. Steganography is one of the security techniques that is used in videos, images, sounds, and other digital data. This technique embeds important data or secret messages into cover media to prevent unauthorized access. This paper proposes a new method for video steganography to develop our security purposes. The proposed method uses integer wavelet transform to increase the security and quality of video frames. This paper also presents an improved three-dimensional Sine chaotic map and uses it in the processes of the proposed video steganography. Hiding different types of messages with various sizes is the main aim of the suggested algorithm. The simulation results show that the proposed method has good imperceptibility and performance after the embedding process. Furthermore, the results of extracted messages after applying some noises on the stego videos, and the regular/singular (RS) steganalysis results demonstrate the acceptable robustness against some noises. Also, comparison results show that the proposed method outperforms some similar approaches.